Toward a theory of transformative entrepreneuring: Poverty reduction and conflict resolution in Rwanda's entrepreneurial coffee sector - Tobias, Jutta; Mair, Johanna; Barbosa-Leiker, Celestina (Elsevier Science B.V., Amsterdam., 2013)
This study illustrates how entrepreneurship may catalyze prosperity as well as peace in entrenched poverty-conflict zones. We bring to life a conceptualization of transformative entrepreneuring by assessing interrelationships between poverty and conflict indicators from the perspective of rural dwellers in Rwanda's entrepreneurial coffee sector. Our findings suggest that individuals' perceptions of poverty alleviation and conflict reduction are sequentially linked, notably via increased quality of life. This enables us to advance theory on entrepreneuring by unpacking the mechanisms through which entrepreneurial processes may transform the lives of such ‘ordinary' entrepreneurs in settings where economic and social value creation are desperately needed.